Vavlilov en Asturias: Una historia en torno a la escanda - Huerga Melcón, Pablo (Nómadas. Critical Journal of Social and Juridical Sciences, 2012)
In the summer of 1927 Vavilov travelled around Spain, searching crops and cultivate plants in order to improve his own Museum in Leningrad. This voyage led Vavilov to Asturias, where he meet with an spanish teacher, González Regueral, who taught him Asturian fields and cultivated plants typical of the area. Regueral, victimized by the spanish war, recalled in the sixties this meeting. The article tells this particular story.